2015
DOI: 10.1097/mpa.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Efficacy of Nonsteroidal Anti-inflammatory Drugs in Preventing Post–Endoscopic Retrograde Cholangiopancreatography Pancreatitis

Abstract: Objectives To identify the factors affecting the efficacy of nonsteroidal anti-inflammatory drugs (NSAIDs) in preventing post–endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP). Methods We systematically searched databases for relevant studies published from inception to November 2013. Results A meta-analysis of 11 randomized trials (n = 2497) revealed a significant reduction in PEP in patients who received NSAIDs compared with that in patients who received placebo (relative risk [RR]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…The trials assessing orally, intraduodenally, intravenously, and intramuscularly given NSAIDs were not significantly associated with a decreased risk of PEP. In addition, the analyses by Rustagi and Njei and by Ding et al . involved the study evaluating the efficacy of valdecoxib, which was reported not to be effective in the prevention of PEP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trials assessing orally, intraduodenally, intravenously, and intramuscularly given NSAIDs were not significantly associated with a decreased risk of PEP. In addition, the analyses by Rustagi and Njei and by Ding et al . involved the study evaluating the efficacy of valdecoxib, which was reported not to be effective in the prevention of PEP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the analysis included studies involving high‐risk patients only . Actually, most of the previous meta‐analyses tended to include both RCT involving unselected patients and RCT involving only high‐risk patients when making the analysis . The most recent meta‐analysis by Inamdar et al .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly though, rectal NSAIDs were only given in high-risk cases at the discretion of the surgeon/ endoscopist and when given, they were not immediately given after ERCP. The latter is relevant as a recent analysis of randomised controlled trials showed that PEP was reduced especially in the group where rectal NSAIDs were given before ERCP [18]. Surprisingly, a recently published randomized controlled trial did not show reduced PEP risks in patients receiving rectal indomethacin [19].…”
Section: Discussionmentioning
confidence: 99%
“…An explanation could be that most of these patients (70%) were of average risk for PEP. Another explanation for the results could be the use of indomethacin as a meta-analysis of 11 randomised controlled trials showed no significant effect of Indomethacin on preventing PEP compared to other NSAIDs [18]. An awaited prospective randomised study of rectal NSAIDs versus rectal NSAIDs and PD stenting in patients at high risk of PEP may help to resolve this important clinical question [20].…”
Section: Discussionmentioning
confidence: 99%
“…In kleineren Studien wird seit zirka zehn Jahren immer wieder der prophylaktische E ekt untersucht -mit unterschiedlichen Ergebnissen, die selbst in Metaanalysen nicht immer kongruent waren [2,3]. Au ällig ist die aus unserer Sicht hohe Rate an Post-ERCPPankreatitiden in den meisten der eingeschlossenen Studien (in den Kontrollgruppen teils weit > 10 %).…”
Section: Gutes Nutzen-/risiko-verhältnis Für Nsar In Der Pankreatitisunclassified